The Effectiveness of Brushing Teeth Video to Improve Autism Parent’s Skill in Brushing Teeth at SLB 2 Provinsi Jambi Year 2020 - Slamet Riyadi; Rosmawati Rosmawati; Mira Sri Gumilar (Jurnal Kesehatan Gigi, 2021)
Childrens with Autism have difficulty to clean their oral cavity because less of ability in motor skills. Case reports show that the average autistic child has dental caries and periodontal disease due to the inability to brush their teeth properly. Autistic children spend a lot of time with their families so that the role of families, especially parents, is very important in the development of children with autism. This study aims to determine the effectiveness of brush teeth video counseling to improve brushing teeth skill in parents of autistic children at SLB 2 Provinsi Jambi. Study design is a quasi experimental study. The independent variable was the video counsellling of brushing teeth and the dependent variable was the parent’s ability of brushing teeth. The Sample in this study were parents of autistic children who met the inclusion and exclusion criteria. The average age of the respondents was 41 years (CI: 38 - 44). Wilcoxon test showed p value 0, 0001 (0.05) means significant difference of brushing skills between treatment group and control group. Mann Whitney showed p value 0.0042 (0.05), means significant difference between before and after intervention in the treatment group. Providing education on brushing skills to children with autism cannot be done instantly, it is necessary for the role of parents in teaching tooth brushing skills to be carried out continuously until children can brush their teeth independently. There is an improvement in brushing skills in parents of autistic children through counseling using videos on how to brush teeth.